Perancangan User Experience Menggunakan Metode Human Centered Design Pada Aplikasi Mobile Portal Berita Tabloidjubi - Naufal Aji Dewananto; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tabloidjubi is a web based news portal originated from Papua Island that publishes National and International news. The increasing of smartphone usage makes Tabloidjubi developed a mobile application. One of the most important aspects of mobile application development is user experience which is useful for user success and user satisfaction when using the application. This research intends to design Tabloidjubi's user experience based on the problems found in the first evaluation. Evaluation method that carried out in this research is heuristic evaluation. The designing of user experience using human centered design method will be held after the problems from the first evaluation are identified. Some of problems found on the first evaluation are intricate categorization and the absence of user features. There is 25 total problems found in the first evaluation. On the second evaluation there is less problems found with total of 5 different problems that differ from the first problems found in the first evaluation. Thus, the problems found in the first evaluation have been successfully solved. The outcome of this research are identification and analysis of the usability problems and advanced design recommendation in the form of high-fidelity prototype as the representation of the given solution.